Learners’ Roadmap through CEFR Reading Test: Challenges, Strategies, and Benefits - Sari, Mila Purnama; Naftali, Lidya Vega; Mardiana, Rizdika (IJECA (International Journal of Education and Curriculum Application), 2025)
The Common European Framework of Reference for Languages (CEFR) is widely recognized as a prominent framework for learning and assessing English proficiency, including in Indonesia. However, fewer ELT professionals in Indonesia are familiar with the CEFR framework than in other Asian countries. Therefore, when English education students from master’s degree programs at one university in Jakarta used the CEFR test to measure their English skills, and to use their learning experience as a reflective activity. This research was conducted to investigate the challenges encountered by the participants in conducting the CEFR reading test, their strategies to cope with them, and the benefits they gained. A qualitative methodology, incorporating ethnography and autoethnography, was employed, with data analyzed through descriptive analysis. The data is taken from three out of the 16 participants, selected purposively for their data completeness, using participants' reflective forms, responses collected via Google Forms, and interviews. The study found that the challenges encountered were primarily due to the combination of the types of questions, the lengthy text, and later technical issues. The vocabulary, grammar, context, and topic do not pose significant challenges. The strategies used by the participants to cope with the struggle included scanning, skimming, rereading the texts multiple times, and utilizing two devices during the test. The study identifies two key benefits: the experience of taking the test itself and the subsequent reflective activity. This reflection allowed participants to identify their strengths and weaknesses, critically evaluate their performance, and implement strategies for improvement, particularly in developing reading skills. Future research could build on these results to create a test-taking strategy program designed to enhance English language proficiency and integrate this knowledge into learning programs.